Anomalous effect of UV light on the humidity dependence of photocurrent in perovskite solar cells. (26th July 2018) - Kumar, Ankit; Mishra, Amrit K; Bansode, Umesh; Ogale, Satishchandra; Rahman, Atikur
Abstract: Effect of oxygen on the humidity dependence of photocurrent in the presence of UV light has been studied for perovskite solar cells. We observed that the magnitude of photocurrent increases with decreasing humidity initially, but below a certain level, the photocurrent starts to decrease when the humidity is reduced by sending dry nitrogen gas. If we decrease the humidity by sending dry air (keeping nitrogen to oxygen ratio same), then this effect is absent. This phenomenon is related to the presence of oxygen in the environment. When humidity is decreased by flowing dry nitrogen, the oxygen present in the environment of perovskite solar cell also reduces. We found that in the reduced oxygen condition, the presence of UV light helps to remove oxygen from the surface of the mesoporous TiO2 which is responsible for the reduction of photocurrent. In the presence of white light, this effect is not observed. To understand the phenomenon we studied low-frequency noise and current–voltage characteristics, and the dielectric properties of perovskite solar cells under various conditions.